FANtastic beyond your imagine / Norhilmi Mohdzahir ...[et al.] - Mohd Zahir, Norhilmi; Yaacob, Ruzilah; Mohamad, Farah Alina; Rahmat, Zurin Nabila; Sayutin, Asmaul Husna; Samaon, Mustain Nasiha (2017)
The invention of FANtastic consists of human motion detector, temperature sensor and automatic ON/OFF switch. It is a bladeless fan and free from noise. This project developed an automatic fan system where speed is controlled by the room temperature. However, it has dual mode operation which are manual and auto. Furthermore, the invention of smart sensing fan can automatically move by detecting near motion in a certain range.